Airway reversibility in newly developed asthma in children - Ariyanto Harsono; Sri Kusumawardani; Makmuri MS; Gunadi Santosa (Indonesian Pediatric Society, 2003)
Objective To determine factors influencing forced expiratory vol-ume in one second (FEV 1 ) reversibility in newly developed asthmain childrenMethods A cross sectional study was done on 52 patients aged 6-14 years who were recruited from a longitudinal study of 161 newlydeveloped asthmatic children. Pre and post-bronchodilator FEV 1were obtained to calculate the reversibility. Seven patients had toperform peak expiratory volume (PEV) variability before recruited.Some variables including sex, age, height, onset of asthma, fre-quency of asthma attacks at the time of the test were analyzed toevaluate their roles in the outcome of FEV 1 reversibility using pairedsample t-test, Pearson’s correlation coefficient, and multi regres-sion analysis.Results Mean pre- and post-bronchodilator FEV 1 were 1.14 (SD0.24) and 1.31 (SD 0.28), respectively. FEV 1 reversibility rangedbetween 6%-36%. Bivariate analyses demonstrated significant cor-relation between either cough (p=0.031) or symptom-free (p=0.041)and the airway reversibility. Multivariate analysis showed that coughwas an important factor influencing airway reversibility (p=0.0246).Conclusion Cough is an important influencing factor of the air-way reversibility